Outcomes of Margin Reexcision after Oncoplastic Breast Reduction. Issue 9 (23rd September 2022) - Martin, Tasha A.; Choudhry, Salman; Holton, Luther H.; Mylander, W. Charles; Tafra, Lorraine; Liang, Wen; Jackson, Rubie Sue
Abstract : Introduction: Tissue rearrangement after an oncoplastic breast reduction may complicate identification of margins during reexcision. Little is known about outcomes of reoperation in this setting. Methods: This is a single-institution, retrospective analysis of outcomes of margin reexcisions after lumpectomy with concurrent oncoplastic Wise-pattern reduction from 2015 to 2020. Outcomes assessed were the rate of successful breast conservation, in-breast recurrence, wound issues or complications, effect on cosmesis, and delay to onset of adjuvant therapy. Results: From 2015 to 2020, 649 patients underwent lumpectomy with oncoplastic Wise-pattern reduction. Forty-seven patients (7.2%) had greater than or equal to one positive margin(s); of these, 28 went directly to mastectomy, and 19 underwent margin reexcision. Residual disease was found in seven of 19 patients (37%) at reexcision. The rate of successful breast-conserving therapy was 95% with a mean follow-up of 31 months. There was one (5%) in-breast recurrence (invasive ductal carcinoma [IDC] occurring 30 months after the original operation); this patient had a mastectomy for treatment of her recurrence. The overall complication rate was 37%. Radiation was administered to 18 patients (95%), and two patients (11%) had delay of radiation past 6 weeks due to wound complications. Of the 14 patients with photographs available, 12 of 14 patients (86%) were blindly assessed to have equivalent or better cosmesis after margin reexcision (versus initial lumpectomy). Conclusion: Margin reexcision after oncoplastic breast reduction with Wise-pattern is feasible and effective, and can be done without compromising the initial cosmetic results.